Optimization of 5 GHz Wi-Fi Network Performance Using Leaky Feeder Cables in Building Infrastructure - Maharani, Vitania; Arinie S, Farida; Hudiono, Hudiono (West Science Interdisciplinary Studies, 2024)
Wi-Fi operates on three frequencies: 2.4 GHz, 5 GHz, and 6 GHz. The 2.4 GHz frequency experiences more interference due to its shared frequency with Bluetooth. Wi-Fi on the 5 GHz frequency encounters less interference but has lower transmission power. This research aims to optimize the 5 GHz Wi-Fi network by utilizing Leaky Feeder cables in the AI building of the State Polytechnic of Malang. The study includes the analysis and design of Leaky Feeder cables, where the access point transmits Wi-Fi signals at a 5 GHz frequency through the leaky feeder cable, which is designed with small slots to allow a small amount of signal energy to leak out. For the farthest signal coverage, the access point reaches a distance of 77 meters with a signal strength of -89 dBm after the installation of the leaky feeder cable. This indicates that the leaky feeder cable has helped extend the access point's signal coverage to a greater distance, albeit with lower signal strength.